2021
DOI: 10.2147/ahmt.s300150
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence for Anhedonia as a Marker of Sexual Trauma in Female Adolescents

Abstract: Introduction Major depressive disorder (MDD) is a common condition with heterogeneous presentations that often include predominant anhedonia. Previous studies have revealed that childhood trauma is a potent risk factor for the development of MDD; however, the clinical implications of this finding are not fully understood. Methods Participants were adolescents (age 13–21 years) with a diagnosis of moderate-to-severe major depressive disorder and healthy controls. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Among individuals with frank psychosis, those who have experienced childhood trauma or early adversity were more likely to report symptoms of anhedonia. 11 A similar relationship between childhood trauma and anhedonia has been found in those experiencing other forms of psychopathology, such as depressive disorders, 12,13 as well as in non-psychiatric controls. 12 However, to our knowledge, the relationship between childhood trauma and anhedonia is yet to be examined in individuals at CHR, as prior research on this population has typically focused on the relationship between childhood trauma and positive symptoms.…”
supporting
confidence: 61%
“…Among individuals with frank psychosis, those who have experienced childhood trauma or early adversity were more likely to report symptoms of anhedonia. 11 A similar relationship between childhood trauma and anhedonia has been found in those experiencing other forms of psychopathology, such as depressive disorders, 12,13 as well as in non-psychiatric controls. 12 However, to our knowledge, the relationship between childhood trauma and anhedonia is yet to be examined in individuals at CHR, as prior research on this population has typically focused on the relationship between childhood trauma and positive symptoms.…”
supporting
confidence: 61%
“… 23 The cut-off values for the presence of CT include emotional abuse ≤8, physical abuse ≤7, sexual abuse ≤5, emotional neglect ≤9 and physical neglect ≤7. 24 The content of the Chinese version of CTQ was consistent with the original version and had a Cronbach’s α coefficient of 0.77. 25 The Cronbach’s α of five subscales ranged from 0.41 (physical neglect) to 0.68 (physical abuse), 25 which is consistent with the original CTQ, reporting a lower Cronbach’s α coefficient (0.45) for physical neglect.…”
Section: Methodsmentioning
confidence: 86%
“…Consistent with previous studies, our study found that adolescent girls experience lower levels of pleasure than boys, and emotional neglect has a greater negative impact on girls’ experience of pleasure than boys’ experience of pleasure. 24 41 These findings may be due to the differences in physical development, such as nervous system development and hormonal regulation, between boys and girls. These differences lead to the different pleasure experiences of adolescents of different sexes.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study was the nonnormal distribution of childhood maltreatment, such that childhood maltreatment was positively skewed, with more participants reporting a history of low maltreatment rather than high maltreatment. While we acknowledge that nonnormal distribution (i.e., positively skewed) of childhood maltreatment is normative in the general population (Etain et al, 2010; Sonmez et al, 2021; Uçok & Bikmaz, 2007), we acknowledge that a priori selection of our sample to have a normal distribution across childhood maltreatment could have avoided some of these interpretation problems. To account for this limitation, we graphed our findings and analyzed simple slopes using the 1st quartile, median, and 3rd quartile values of childhood maltreatment rather than the mean and one standard deviation above and below the mean.…”
Section: Discussionmentioning
confidence: 99%